A thermal theory for flammability diagrams guiding purge and inertion of a flammable mixture. Issue 1 (27th November 2012) - Ma, Tingguang
<x xml:space="preserve">Abstract</x> Recently, a thermal method was proposed to recheck the concept of flammability by manipulating the competition between heating and quenching. This method is further explored here to reconstruct flammability diagrams, explaining the contribution of each component toward flammability change for a mixture. Based on the assumption that a diluent will not change the flame temperature at the flammability limits, these isothermal processes lead to a conservative estimation of the flammable zone. Although rough near the inertion point, the theoretical flammability envelop has the potential to guide future purging and diluting operations. It will be a powerful tool for both educational purposes and practical utilities. © 2012 American Institute of Chemical Engineers Process Saf Prog 32: 42–48, 2013